Gender under fire: portrayals of military women in the Australian print media. Issue 2 (17th February 2020) - Bridges, Donna; Wadham, Ben
ABSTRACT: The news media is historically recognised for producing and reinforcing gendered norms and binaries. Correspondingly militaries are institutions where gender roles and expectations create contention. We conducted a content analysis of two Australian broadsheets; the Australian and the Sydney Morning Herald . We investigated how military women were represented between 1997 and 2017, exploring three categories (1). Gendered violence (2). Combat (3). Organisational. This article examines findings about Gendered violence which was reported on substantially more than the other categories; the act of silencing women's voice and experience was highest here when the author was male. The "Skype Affair" attracted considerable media attention and whilst reporting did not sensationalise violence against women, reporters engaged in journalistic devices that diminished the perpetrator/s role whilst positioning the victim centrally; using "hijacking" maneuvers to prioritise stories about men, omit women's agency, and provide a smokescreen to conceal the dysfunction of institutional gendered violence within the military. Feminism and feminist commentary was poorly represented, providing no meaningful contribution within the sample. We conclude that the focus on women as sexual beings and victims in the print media in Australia reproduces stereotypes of gender roles that create and perpetuate gender inequalities.